PARTISIPASI MASYARAKAT DALAM MUSRENBANG: ANALISA BERDASARKAN TEORI MOBILISASI SUMBER DAYA - Ka'Issa, Adestima; Tulis, Riamona Sadelman; Setiawan, Ferry; Hikmah, Nurul; Selvia, Fitriana (Universitas Djuanda, 2024)
Community participation in development is essential to ensure program sustainability and relevance. Active community involvement leads to policies that reflect their needs, increasing effectiveness. This research aimed to explore the factors that influence community participation in Musrenbang in Bayat Village by using the perspective of Resource Mobilization Theory. This study identifies the available material, human, and non-material resources and their use in Musrenbang. Using a qualitative approach, data was collected through observation, in-depth interviews, and documentation studies with key informants: the village head, village officials, and community leaders. The findings demonstrated that mobilizing material resources supplied by the village government, such as budget, meeting facilities, planning information, and transportation, might inspire changes in community enthusiasm to actively participate in Musrenbang. Furthermore, human resources such as facilitators and community leaders play a significant role in organizing community engagement. This research discovered that efficient resource mobilization strategies help bridge the gap between planning and implementation of village development. The provision of financial compensation and recognition of community status also increases the motivation to actively participate in Musrenbang. This study offers new insights into the dynamics of community participation in Musrenbang in Bayat Village and underscores the importance of appropriate resource utilization in the village development process.